2013
DOI: 10.1590/s0103-05822013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of low birthweight infants in Taubaté, São Paulo, Brazil

Abstract: OBJECTIVE: To identify the spatial pattern of low birth weight infants in the city of Taubaté, São Paulo, Southeast Brazil. METHODS: Ecological and exploratory study, developed with the data acquired from the Health Department of Taubaté, regarding the period from January 1st 2006 and December 31st 2010. Birth certificates were used to obtain the data from infants weighing less than 2500g. A digital basis of census tracts was applied and the Global Moran index (IM) was estimated. Thematic maps were built for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The spatial autocorrelation analysis revealed that low birth weight had spatial dependency (Moran'I=0.56, p-value: 0.01) in Ethiopia. This result was in agreement with studies done in upper-and middle-income countries (17,(31)(32)(33) where low birth weight had shown significant spatial clustering across different regions within respective countriess. This might be due to the variation in maternal health service utilization during pregnancy and variation in health service coverage across different regions in Etiopia.…”
Section: Discussionsupporting
confidence: 93%
“…The spatial autocorrelation analysis revealed that low birth weight had spatial dependency (Moran'I=0.56, p-value: 0.01) in Ethiopia. This result was in agreement with studies done in upper-and middle-income countries (17,(31)(32)(33) where low birth weight had shown significant spatial clustering across different regions within respective countriess. This might be due to the variation in maternal health service utilization during pregnancy and variation in health service coverage across different regions in Etiopia.…”
Section: Discussionsupporting
confidence: 93%
“…Most mothers had single pregnancies in 97.30% of all live births, appropriate gestational age, pregnancies to term in 88.90% (1,193,226) of the cases, and 56.50% (758,882) had a cesarean section. Twin and triplet pregnancies or more were determining factors in the prevalence of LBW in 62.90% and 96.90% of the cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The association between low birth weight and prematurity is described in several studies (1,(3)(4)(5)(6)(7) , however there is one study that identifies that this association is inadequate. The authors (12) report that prematurity may be related to incorrect calculation of the probable date of delivery and to the increased occurrence of cesarean deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Spatial analysis is a great importance for the public health since it helps in the diagnosis and the planning in the affected areas through the geographic characteristic of the disease. 6 This tool has been used in several types of studies in varied themes in the pediatric area, such as the spatial analysis of hospitalizations due to pneumonia and burns in Mato Grosso State, 7 in the distribution of newborns with low birth weight, 8 in neonatal mortality, 9 and other themes for the interest in public health, such as fatal victims in traffic accidents 10 and the identification of risky areas for schistosomiasis mansoni. 11 The objective of this study is to identify the spatial patterns of hospitalization due to diarrhea in children 0 to 4 years old in the counties in São Paulo State, between 2008 and 2012.…”
Section: Introductionmentioning
confidence: 99%